TiO2 supported single Ag atoms nanozyme for elimination of SARS-CoV2 - Wang, Daji; Zhang, Bin; Ding, Hui; Liu, Dan; Xiang, Jianquan; Gao, Xuejiao J.; Chen, Xuehui; Li, Zhongjun; Yang, Lei; Duan, Hongxia; Zheng, Jiyan; Liu, Zheng; et al. (Nano today, 2021)
•A TiO2 supported Ag atoms single atom nanozyme (Ag-TiO2 SAN) was rationally designed.•Ag-TiO2 SAN is produced by gram-scale synthesis and low cost comparing to traditional nanozymes.•Ag-TiO2 SAN performs efficient adsorption for SARS-CoV2 via interaction between Ag atoms and surficial Cys and Asn of S1 RBD.•Ag-TiO2 SAN is swallowed by macrophages and subsequently performs high peroxidase-like activity in lysosome.•Ag-TiO2 SAN exhibits promising anti-viral activity and biocompatibility in vivo. [Display omitted] The outbreak of SARS-coronavirus 2 (SARS-CoV2) has become a global health emergency. Although enormous efforts have been made, there is still no effective treatment against the new virus. Herein, a TiO2 supported single-atom nanozyme containing atomically dispersed Ag atoms (Ag-TiO2 SAN) is designed to serve as a highly efficient antiviral nanomaterial. Compared with traditional nano-TiO2 and Ag, Ag-TiO2 SAN exhibits higher adsorption (99.65%) of SARS-CoV2 pseudovirus. This adsorption ability is due to the interaction between SAN and receptor binding domain (RBD) of spike 1 protein of SARS-CoV2. Theoretical calculation and experimental evidences indicate that the Ag atoms of SAN strongly bind to cysteine and asparagine, which are the most abundant amino acids on the surface of spike 1 RBD. After binding to the virus, the SAN/virus complex is typically phagocytosed by macrophages and colocalized with lysosomes. Interestingly, Ag-TiO2 SAN possesses high peroxidase-like activity responsible for reactive oxygen species production under acid conditions. The highly acidic microenvironment of lysosomes could favor oxygen reduction reaction process to eliminate the virus. With hACE2 transgenic mice, Ag-TiO2 SAN showed efficient anti-SARS-CoV2 pseudovirus activity. In conclusion, Ag-TiO2 SAN is a promising nanomaterial to achieve effective antiviral effects for SARS-CoV2.